A modifiable double donor based on bis(N-ethyl-N-hydroxyethyl)aniline for organic optical nonlinear chromophores. (17th March 2022) - Zeng, Qingzhu; Chen, Xunyu; Rahman, Abdul; Zeng, Ziying; Liang, Zhiwei; Shi, Lei; Huang, Zeling; Bo, Shuhui; Liu, Fenggang; Wang, Jiahai
Abstract : A strong modifiable double donor based on a bis( N -ethyl- N -hydroxyethyl)aniline-derived structure was developed and applied to nonlinear optical materials which show a large r 33 value of 351 pm V −1 for the first time. Abstract : A strong modifiable double donor based on a bis( N -ethyl- N -hydroxyethyl)aniline-derived structure was developed and applied to nonlinear optical materials for the first time. Three isolation groups were introduced into the donor and bridge sides of the chromophores to reduce the electrostatic interaction between molecules, so as to improve the poling efficiency. Based on this, we have developed a series of nonlinear optical chromophores BLD1-4 with the same bis( N -ethyl- N -hydroxyethyl)aniline-based donor and TCF or CF3 –TCF acceptor with isophorone-derived bridges. Density functional theory calculations suggested that the four chromophores have much larger hyperpolarizability than traditional nonlinear optical chromophores due to the strong electron donor ability. Poled films of neat chromophores BLD1–BLD4 showed very high poling efficiencies due to the large steric hindrance and first-order hyperpolarizability of the chromophores. An ultrahigh r 33 (351 pm V −1 ) and poling efficiency (3.50 ± 0.10 nm 2 V −2 ) at 1310 nm have been achieved for the neat film containing chromophore BLD3. The large electro-optic coefficient makes these new donors very promising in the theory-guided design of organic nonlinear optical materials.